Oil spill protection plan: The use of geographical information system (GIS) in storing and accessing coastal sensitivity index - Said, Mohamad Nor (2001)
The Straits of Malacca has been one of the busiest international waterways since a very long time as it links the navigational channels between the western side of the world to the Asia Pacific region. The volume of traffic keeps increasing every year and so do the number of accidents at sea, among which involving oil tankers passing through the straits, thus making oil pollution as a significant threat to the Malaysian Peninsular water. With an abundance of tremendous economic value of coastal and marine natural resources as well as the heavy fishing industries and tourism activities, a more systematic plan is realized to be necessary to protect the coast from being damaged by the oil in the case of any accident. However, no effective planning process can be carried out without having an up-to-date and accurate information. Thus, a map showing oil-sensitivity index is required in order to serve as a quick reference for the coastal zone managers and more importantly for the oil-spill responders to take action when the spill occurs. A pilot study to produce an Environmental Sensitivity Index (ESI) map was carried by a research team from the Universiti Teknologi Malaysia (UTM) recently. The project was sponsored by the Japan Wildlife Research Center (JWRC) with a specific study to map the location of oil-sensitive wildlife in the selected study area. Larut Matang, an area of western side of the state of Perak was chosen as the study site of the project. The choice was made for some reasons: (1) the area contains mangroves which are one of the oil-sensitive species; (2) the mangrove forests as well as the surrounding mudflat areas have been an attraction to many species of local and migratory birds which are vulnerable to oil; (3) considerably large fishing industry especially aquaculture makes the area so important to the local economy, hence any oil spill will certainly leave a considerable amount of effects. Three environmental elements were identified to be included in the ESI map. First is the shoreline classes which are ranked according to their sensitivity, the natural persistence of oil and the ease of cleanup. Based on the index produced by the United States, three types of shorelines were identified and classified to be either less sensitive, moderately sensitive or highly sensitive (ESI) to oil. The second environmental element is the biological resources which include animal species comprising birds (local and migratory), mammals (terrestrial and sea), fish (including cage farmed), cockles and reptiles/ amphibians. Thirdly, the location of human-use was also mapped to support the other information. This includes the recreational and protected areas, shoreline access as well as the available emergency services in the surrounding areas. Having recognized the environmental elements associated with the proposed ESI map, a database was established. This was done digitally using functionalities available within a Geographical Information System (GIS) and by other mapping technology such as satellite image processing system. Both spatial and attribute data were stored in a GIS database which were then linked for the purpose of query and display. Suitable symbols were created to show the location of the associated oil-sensitive features. A simple and easy-to-use interface was also developed to assist the map user retrieving any desired information from the ESI map.